Simultaneous quarter-wave plate and half-mirror operation through a highly flexible single layer anisotropic metasurface - Khan, M. Ismail; Tahir, Farooq A. (Scientific reports, 2017)
A highly flexible single-layer metasurface manifesting quarter-wave plate as well as half-mirror (1:1 beam-splitter) operation in the microwave frequency regime is being presented in this research. The designed metasurface reflects half power of the impinging linearly polarized electromagnetic wave as circularly polarized wave while the remaining half power is transmitted as circularly polarized wave at resonance frequency. Similarly, a circularly polarized incident wave is reflected and transmitted as linearly polarized wave with equal half powers. Moreover, the response of the metasurface is quite stable against the variations in the incidence angle up to 45°. The measurements performed on the fabricated prototype exhibit a good agreement with the simulation results. The compact size, flexible structure, angular stability and two in one operation (operating as a quarter-wave plate and beam-splitter at the same time) are the main characteristics of the subject metasurface that makes it a potential candidate for numerous applications in communication and miniaturized and conformal polarization control devices.